2007
DOI: 10.1098/rstb.2007.2179
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for abiotic stresses for sustainable agriculture

Abstract: Using cereal crops as examples, we review the breeding for tolerance to the abiotic stresses of low nitrogen, drought, salinity and aluminium toxicity. All are already important abiotic stress factors that cause large and widespread yield reductions. Drought will increase in importance with climate change, the area of irrigated land that is salinized continues to increase, and the cost of inorganic N is set to rise. There is good potential for directly breeding for adaptation to low N while retaining an abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
162
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(167 citation statements)
references
References 162 publications
(203 reference statements)
4
162
0
1
Order By: Relevance
“…With a projected increase in drought with climate change, the breeding for drought-tolerant crops is even more emphasised (Witcombe et al, 2008). In addition to drought, temperature-induced stress causes variability in wheat yields (Semenov and Shewry, 2011;Asseng et al, 2011), corn and soybean (Schlenkera and Roberts, 2009) and other crops (e.g.…”
mentioning
confidence: 99%
“…With a projected increase in drought with climate change, the breeding for drought-tolerant crops is even more emphasised (Witcombe et al, 2008). In addition to drought, temperature-induced stress causes variability in wheat yields (Semenov and Shewry, 2011;Asseng et al, 2011), corn and soybean (Schlenkera and Roberts, 2009) and other crops (e.g.…”
mentioning
confidence: 99%
“…In this context, it was observed that plants can present mechanisms or strategies of tolerance and susceptibility that are expressed during their developmental stages (Osmond et al, 1097;Lichtenthaler, 1996;Chaves et al, 2003). Different mechanisms and processes are involved in order to avoid the effects of drought and promote tolerance, among which phenology is considered one of the essential factors because water stress is highly variable in duration and severity (Witcombe et al, 2008). In regard to plant evolution, water availability is classified as the most relevant factor among elements which collaborate to abiotic stresses.…”
Section: Water Deficitmentioning
confidence: 99%
“…Salinity and drought stresses are among the most serious challenges to crop production in the world today, particularly in developing countries (Zhou et al, 2007). Drought and salinity tolerance can be designated as complex traits due to the interplay of multiple pathways that mediate a plant's capacity to withstand these abiotic stresses (Witcombe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%